The Role Of Career Women In Islamic Children's Education - Nursoidah (MAQOLAT: Journal of Islamic Studies, 2023)
Women's career is a problem in itself from various eras, especially the patriarchal culture that is embedded in society. Where are women's activities only taking care of the household not far from wells, mattresses and kitchens. While on the other hand women also have more potential that can compete with men in the outside world. There are even some jobs that are better done by women than men. Even so, women also have more important obligations, this is in accordance with Islamic teachings that a woman's duty is to educate children and serve her husband. Based on the reality above, research seeks to explore the concept of thinking that exists in society about a woman's career and her main task in taking care of the family. So that in relation to the researcher can formulate some existing problem formulations, namely how are career women in the view of Siti Muri'ah?. Second, what is the method of educating children according to Islam? This article is made for how career women divide their duties as a mother and as an important part of society. The second is input for parents to innovate in children's education which is applied by the family, especially a woman who has a career in educating her child. And provide information to parents, especially career women, about their children's education. This research is library research and character study. The conclusion of this study is that Islam obliges men as husbands to meet the needs of their wives and children, but this does not abort a woman's obligation as a wife morally to help her husband earn a living. In children's education, children are entrusted to both parents, meaning that not only is a mother obligatory in terms of educating children but fathers must also work hand in hand in educating their children. A family must share roles and work hand in hand in fostering a family so that the family continues to live harmoniously and prosper in the future.